Simultaneous occurrence of inflammatory bowel disease and trichomonosis in a Maine coon cat - Santos, César A R; Melo, Jéssica C; Sampaio, Letícia H T S; Ferari, Lorena C.; Moura, Fernanda B C; Souza, Fúlvia B; Kobayashi, Priscila E.; Fonseca-Alves, Carlos E.; Okamoto, Priscylla T C G; Rahal, Sheila C.; Melchert, Alessandra (My University, 2022)
A 2-year-old, 4.2 kg, spayed female, Maine coon cat was referred to the veterinary hospital for evaluation of hyporexia, slow growth, and chronic, intermittent, mucoid, bloody, voluminous, and fetid diarrhea. The diarrhea had been observed since the cat was acquired from a cattery at 4 months of age; with acute worsening in the 5 d before presentation. Abdominal palpation revealed moderate pain. Ultrasonographic examination showed thickening of the jejunal wall and ileal loops, increased echogenicity of the jejunal mucosa, and enlargement of the jejunal and ileocolic lymph nodes. Histopathology of full-thickness intestinal biopsies showed moderate, diffuse, lymphoplasmacytic, erosive enteritis with hemorrhage and edema. Diffuse, lymphoplasmacytic, erosive colitis with mild, interstitial fibrosis and hemorrhage was also noted. The ileocecal lymph node biopsy showed eosinophilic lymphadenitis. Based on the immunohistochemical evaluation of intestinal samples with CD3 and CD79a antibodies, a diagnosis of lymphoma was ruled out. Fecal polymerase chain reaction testing was positive for Tritrichomonas foetus. Based on these results, inflammatory bowel disease and trichomonosis were diagnosed. Treatment for the cat included a hypoallergenic diet and an oral omega-3 fatty acid supplement, in conjunction with prednisolone, to manage the inflammatory bowel disease. Ronidazole was administered to target the Tritrichomonas foetus. The cat was clinically normal during a follow-up examination after 6 months of treatment.

Apparition simultanée d’une maladie inflammatoire de l’intestin et d’une trichomonose chez un chat Maine coon. Une chatte Maine coon de 2 ans, pesant 4,2 kg, stérilisée, a été référée à l’hôpital vétérinaire pour une évaluation d’hyporexie, de croissance lente et de diarrhée chronique, intermittente, mucoïde, sanglante, volumineuse et fétide. La diarrhée avait été observée depuis que le chat avait été acquis en chatterie à l’âge de 4 mois; avec une aggravation aiguë dans les 5 jours avant la présentation. La palpation abdominale a révélé une douleur modérée. L’examen échographique a montré un épaississement de la paroi jéjunale et des anses iléales, une augmentation de l’échogénicité de la muqueuse jéjunale et une hypertrophie des ganglions lymphatiques jéjunaux et iléocoliques. L’histopathologie des biopsies intestinales de pleine épaisseur a montré une entérite modérée, diffuse, lymphoplasmocytaire, érosive avec hémorragie et oedème. Une colite érosive diffuse, lymphoplasmocytaire avec fibrose interstitielle légère et hémorragie a également été notée. La biopsie ganglionnaire iléo-caecale montrait une lymphadénite à éosinophiles. Sur la base de l’évaluation immunohistochimique d’échantillons intestinaux avec des anticorps CD3 et CD79a, un diagnostic de lymphome a été écarté. Le test de réaction en chaîne par la polymérase sur les matières fécales était positif pour Tritrichomonas foetus. Sur la base de ces résultats, une maladie inflammatoire de l’intestin et une trichomonose ont été diagnostiquées. Le traitement du chat comprenait un régime hypoallergénique et un supplément oral d’acides gras oméga-3, en association avec de la prednisolone, pour gérer la maladie inflammatoire de l’intestin. Le ronidazole a été administré pour cibler Tritrichomonas foetus. Le chat était cliniquement normal lors d’un examen de suivi après 6 mois de traitement.(Traduit par Dr Serge Messier).